The Demand Side of Jobs in Indonesia : Plant-level Analysis in the Medium and Large Manufacturing Industry - Wihardja, Maria Monica; Alatas, Hamidah (World Bank, Washington, DC, 2021)
This study is motivated by the lack of demand-side jobs study in Indonesia. Workers do not create jobs; they only fill job openings. However, most of the jobs studies in Indonesia are focused on the supply side of jobs (workers), including skills development, workers protection and unemployment insurance, as well as international migration. To gain insights into the job-creation side of the puzzle, this study proposes to explore the demand side of jobs (employers or firms). Specifically, it aims to contribute to the Indonesia Jobs Strategy by providing new (and perhaps the only) evidence on the demand side of jobs in Indonesia. This report is not exhaustive of all demand side of jobs. It is part of the bigger report on demand-side jobs, which will include the macroeconomic analysis (growth and productivity decomposition, projected sectoral employment growth, etc.), HH enterprises (including those in the agriculture sector), and the emerging economic sectors such as the digital economy.